On the design of integrated thermal management systems for eVTOL aircraft - Kang, Sangkeun; Saias, Chana Anna; Roumeliotis, Ioannis; Broca, Olivier (American Society of Mechanical Engineers (ASME), 2023)
Vertical take-off and landing aircraft equipped with hybrid or fully electric propulsion systems have gained interest for urban air mobility applications. Besides the low energy density of state of art electric systems, their strict operating temperature requirement and low-grade heat highlight the importance of effective thermal management system design. This paper aims to establish a design process for the thermal management system for a parallel hybrid electric tiltrotor and showcase it for a system consisting of direct ram-air cooling cold plate and phase change materials. The cold plate is designed for cruise conditions and used as heat acquisition and cooling system, whereas the phase change materials is used as a heat storage system when ram air is limited. Three sizing conditions are considered comprising the baseline design mission, a certification condition for One Engine Inoperative (OEI) and an off-design mission. The effects of thermal management system integration on overall performance are quantified and discussed. The results indicate that designing the system for the baseline sizing mission results in a 5% increase in fuel burn per payload relative to the equivalent counterpart without thermal management consideration. This penalty increases to 14% when certification requirements are accounted. It is highlighted that tor shorter mission thermal management is the limiting factor for battery utilization, hence the expected benefits are significantly reduced. As electric components technology increases thermal management becomes less sensitive to the sizing conditions.
Keywords: rotorcraft; hybrid-electric propulsion; thermal management system; cooling system; heat loads